2020
DOI: 10.1111/cts.12805
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Autoimmune Characteristics of Severe and Critical Cases of COVID‐19

Abstract: In this study we report on the clinical and autoimmune characteristics of severe and critical novel coronavirus pneumonia caused by severe acute respiratory syndrome-associated coronavirus 2 (SARS-CoV-2). The clinical, autoimmune, and laboratory characteristics of 21 patients who had laboratory-confirmed severe and critical cases of coronavirus disease 2019 (COVID-19) from the intensive care unit of the Huangshi Central Hospital, Hubei Province, China, were investigated. A total of 21 patients (13 men and 8 wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
255
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 269 publications
(296 citation statements)
references
References 7 publications
12
255
1
4
Order By: Relevance
“…For lymphocyte, although one of the studies [19] showed that patients with sCOVID-19 had higher lymphocyte count compared to non-severe COVID-19 ones (MD = 0.01 [-0.34,0.36]), the pooled results of thirteen studies [15,16,18,19,[22][23][24][25][26][28][29][30]32] showed that lymphocyte count in patients with sCOVID-19 was signi cantly lower compared to non-severe COVID-19 patients (MD = -0.38 [-0.47,-0.29], p-value < 0.0001) ( Fig 2B). In twelve studies [15,18,19,[22][23][24][25][26][28][29][30]32], patients with severe conditions had signi cantly higher neutrophil count than those with non-severe complications (MD = 2.01 [1.22,2.80], p-value = 0.005) ( Fig 2C). The results of xed-effects meta-analysis on the ten studies [15,16,18,19,[22][23][24]26,28,30] showed that platelet count in patients with sCOVID-19 was signi cantly lower compared to patients with non-severe COVID-19 (MD = -11.7 [-23.03,-0.38], p-value = 0.042) ( Fig 2D).…”
Section: Blood Cell Parametersmentioning
confidence: 99%
See 4 more Smart Citations
“…For lymphocyte, although one of the studies [19] showed that patients with sCOVID-19 had higher lymphocyte count compared to non-severe COVID-19 ones (MD = 0.01 [-0.34,0.36]), the pooled results of thirteen studies [15,16,18,19,[22][23][24][25][26][28][29][30]32] showed that lymphocyte count in patients with sCOVID-19 was signi cantly lower compared to non-severe COVID-19 patients (MD = -0.38 [-0.47,-0.29], p-value < 0.0001) ( Fig 2B). In twelve studies [15,18,19,[22][23][24][25][26][28][29][30]32], patients with severe conditions had signi cantly higher neutrophil count than those with non-severe complications (MD = 2.01 [1.22,2.80], p-value = 0.005) ( Fig 2C). The results of xed-effects meta-analysis on the ten studies [15,16,18,19,[22][23][24]26,28,30] showed that platelet count in patients with sCOVID-19 was signi cantly lower compared to patients with non-severe COVID-19 (MD = -11.7 [-23.03,-0.38], p-value = 0.042) ( Fig 2D).…”
Section: Blood Cell Parametersmentioning
confidence: 99%
“…Based on the described search strategy, a total of 26151 studies were identi ed in the three searched online databases. Following the removal of duplicates and screening all records, 18 studies meeting the predetermined eligibility criteria were imported in the meta-analysis [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. The article number and reason for exclusion in each screening steps are depicted in Fig 1. Accumulatively, 2459 patients were included in the quantitative analysis, among which 710 patients were in severe/critical condition, and the rest (1737 cases) classi ed as mild/moderate disease.…”
Section: Study Selection and Baseline Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations